Exploring Effective Methods for Introducing Phonology to Beginner Learners: A Comprehensive Literature Review - Fahima Mashalani; Yani Lubis; Miftahul Jannah (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
The research aims to identify the best method for Introducing phonology to beginners. The author of this study defined vital terms such as phonology and instructional approaches after analyzing appropriate sources and previous research. It explained how to introduce phonology using qualitative methods. It also answers the discussion and the question, "what is the most suitable method for beginners” After presenting the methods applied by the Fadhlul Qurro Islamic Boarding School participants for data collection, analysis, and outcomes, the researcher also discusses the results and concludes.This research was based on a comprehensive literature review on English phonology for second language learners. This approach does not involve empirical research or collecting new primary data but gathers information from relevant secondary sources such as textbooks, academic journals, online articles, and other trusted sources. The first step we took in this research method was to identify and select sources related to English phonology for second-language learners. These sources are then analyzed systematically to obtain an easily understood understanding. In the analysis process, we identify and evaluate English phonology for second language learners using relevant sources and analyze them to support the concepts. We also look at what problems students teaching English as a second language often find and how to overcome the problems. In addition, in this research method, we compare and rearrange information found in the literature to ensure that the information presented in this journal is consistent, accurate, and easy to understand.